Citric acid of ovarian cancer metabolite induces pyroptosis via the caspase‐4/TXNIP‐NLRP3‐GSDMD pathway in ovarian cancer. Issue 6 (24th May 2022) - Wang, Xiaogang; Yin, Yuxin; Qian, Wei; Peng, Chen; Shen, Sunan; Wang, Tingting; Zhao, Shuli
Abstract: Malignant tumors display profound changes in cellular metabolism, yet how these altered metabolites affect the development and growth of tumors is not fully understood. Here, we used metabolomics to analyze the metabolic profile differences in ovarian cancer and found that citric acid (CA) is the most significantly downregulated metabolite. Recently, CA has been reported to inhibit the growth of a variety of tumor cells, but whether it is involved in pyroptosis of ovarian cancer and its potential molecular mechanisms still remains to be further investigated. Here, we demonstrated that CA inhibits the growth of ovarian cancer cells in a dose‐dependent manner. RNA‐seq analysis revealed that CA significantly promoted the expression of thioredoxin interacting protein (TXNIP) and caspase‐4 (CASP4). Morphologic examination by transmission electron microscopy indicated that CA‐treated ovarian cancer cells exhibited typical pyroptosis characteristics. Further mechanistic analyses showed that CA facilitates pyroptosis via the CASP4/TXNIP‐NLRP3‐Gesdermin‐d (GSDMD) pathway in ovarian cancer. This study elucidated that CA induces ovarian cancer cell death through classical and non‐classical pyroptosis pathways, which may be beneficial as an ovarian cancer therapy.